The GOOD COOPERATIVE GOVERNANCE ANALYSIS FOR FRAUD PREVENTION IN COOPERATIVE FINANCIAL REPORTING PROCESSES - Nurul Handayani; Ainiyah, Ghonimah Zumroatun (Realible Accounting Journal, 2026)
This study aims to analyze the effect of the implementation of transparency and accountability as a form of fraud prevention in the preparation of financial reports at KSP Berkah Sesama Jatim, Sidoarjo Branch. The research method uses a qualitative case study approach. Data collection was conducted through interviews and documentation, analysis refers to the theory of Miles & Huberman. The results of the study indicate that the implementation of transparency in the preparation of financial reports has been implemented. The evidence is that financial reports can be accessed as needed and can be tracked in real time in the Core Banking System. The Annual Members Meeting (RAT) is also held routinely every year. The application of the principle of accountability in the preparation of financial reports has also been implemented. Only improvements are needed in the documentation of corrections and evaluations. Overall, both principles of GCG have been implemented and proven to have a direct impact on fraud prevention in the preparation of financial reports at KSP Berkah Sesama Jatim, Sidoarjo Branch. To minimize the risk of fraud as much as possible, the Cooperative is advised to strengthen the implementation of GCG, provide HR training, and conduct external audits with KAP.